2023
DOI: 10.3389/fcell.2022.1059579
|View full text |Cite
|
Sign up to set email alerts
|

Organoid factory: The recent role of the human induced pluripotent stem cells (hiPSCs) in precision medicine

Abstract: During the last decades, hiPSC-derived organoids have been extensively studied and used as in vitro models for several applications among which research studies. They can be considered as organ and tissue prototypes, especially for those difficult to obtain. Moreover, several diseases can be accurately modeled and studied. Hence, patient-derived organoids (PDOs) can be used to predict individual drug responses, thus paving the way toward personalized medicine. Lastly, by applying tissue engineering and 3D prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 127 publications
0
12
0
Order By: Relevance
“…Understanding the physiology and pathology of many hard tissue diseases can be gained by examining the mineral composition of hard tissue organoids and how they vary over time. The mineralization process, which the authors discovered, was comparable to genuine bone, and the organoids showed more significant mineralization with time, similar to natural bone [12][13][14]. Furthermore, hydroxyapatite crystals are deposited within a collagen matrix as part of the complicated and dynamic process of bone mineralization [15].…”
Section: Introductionmentioning
confidence: 74%
“…Understanding the physiology and pathology of many hard tissue diseases can be gained by examining the mineral composition of hard tissue organoids and how they vary over time. The mineralization process, which the authors discovered, was comparable to genuine bone, and the organoids showed more significant mineralization with time, similar to natural bone [12][13][14]. Furthermore, hydroxyapatite crystals are deposited within a collagen matrix as part of the complicated and dynamic process of bone mineralization [15].…”
Section: Introductionmentioning
confidence: 74%
“…Because ALS symptoms progress rapidly and daily physical activities become impossible for patients within 1-2 years, rapid establishment of patient-derived iPSCs and drug screening of MNs are essential for precision medicine. Although there are many problems to be solved in the practical application of personalized medicine using iPS cells (Shin et al, 2018, Novelli et al, 2023, Palasantzas et al, 2023, Nguyen et al, 2023, we believe that our method can shorten the time required for drug screening and contribute to practical application.…”
Section: Discussionmentioning
confidence: 93%
“…Here, we leveraged gene editing in human keratinocytes and an organotypic epidermal model to elucidate the pathogenic mechanisms underlying a rare genetic disorder, which allowed us to identify much-needed potential therapeutic avenues. Though testing if our findings translate to an effective treatment approach for patients remains to be done, our work nevertheless underscores the power of organoids to generate large-scale transcriptomic and proteomic datasets that can be mined for rational drug targets to validate both in vitro and in patient-derived tissues (77,(79)(80)(81)(82).…”
Section: Discussionmentioning
confidence: 94%
“…The copyright holder for this preprint this version posted March 7, 2023. ; https://doi.org/10.1101/2023.03.07.531620 doi: bioRxiv preprint proteomic datasets that can be mined for rational drug targets to validate both in vitro and in patient-derived tissues (77,(79)(80)(81)(82).…”
Section: Discussionmentioning
confidence: 99%